Hijra and Jihad in Classical Islam - Ebstein, Michael (Jama'a: an Interdisciplinary Journal of Middle East Studies, 2006)
Two types of hijra are discussed in early Islamic sources: the Prophet’s emigration from Mecca to al-Medina in 622, and the emigration of Muslims to garrison towns during the conquests of the first century A.H. This article examines the relationship between the concept of hijra (in its double meaning) and the religious duty of jihad in Classical Islam. It aims to uncover the evolution of this relationship as reflected in the Qur’an, in hadith literature (regarded here as a product of the first two centuries of Islamic history), and in the discussions of Muslim jurists and hadith experts. Using this prism, the author reveals religious, political, and social processes of the first two centuries of Islamic history, such as the fluctuation in the social status of the nomadic Arabs.